In situ Gelling Amphotericin B Nanofibers: A New Option for the Treatment of Keratomycosis - Göttel, Benedikt; Lucas, Henrike; Syrowatka, Frank; Knolle, Wolfgang; Kuntsche, Judith; Heinzelmann, Joana; Viestenz, Arne; Mäder, Karsten (Frontiers in Bioengineering and Biotechnology, 2020)
The purpose of our research was the development of Amphotericin B-loaded in situ gelling nanofibers for the treatment of keratomycosis. Different formulation strategies were applied to increase the drug load of the sparingly water-soluble Amphotericin B in electrospun Gellan Gum/Pullulan fibers. These include bile salt addition, encapsulation in poly(lactic-co-glycolic acid) (PLGA) nanoparticles and formation of a polymeric Amphotericin B polyelectrolyte complex. The Amphotericin B polyelectrolyte complex (AmpB-Eu L) performed best and was very effective against the fungal strain Issatchenkia orientalis in vitro. The complex was characterized in detail by attenuated total reflection infrared spectroscopy, X-ray powder diffraction and differential scanning calorimetry. A heat induced stress test was carried out to ensure the stability of the polyelectrolyte complex. To gain information about the cellular tolerance of the developed polyelectrolyte complex a new, innovative multilayered-stratified human cornea cell model was used for determination of the cellular toxicity in vitro. For a safe therapy, the applied ophthalmic drug delivery system has to be sterile. Sterilization by electron irradiation caused not degradation of pure Amphotericin B and also for the bile salt complex. Furthermore, the developed Amphotericin B polyelectrolyte complex was not degraded by the irradiation process. In conclusion, a new polyelectrolyte Amphotericin B complex has been found which retains the antifungal activity of the drug with sufficient stability against irradiation-sterilization induced drug degradation. Furthermore, in comparison with the conventional used eye drop formulation, the new AmpB-complex loaded nanofibers were less toxic to cornea cells in vitro. Electrospinning of the Amphotericin B polyelectrolyte complex with Gellan Gum/ Pullulan leads to the formation of nanofibers with in situ gelling properties, which is a new and promising option for the treatment of keratomycosis.